Application of the Graph Theory in Managing Power Flows in Future Electric Networks - Nguyen, P. H.; Kling, W. L.; Georgiadis, G.; Papatriantafilou, M.; Tuan, L. A.; Bertling, L. (IntechOpen, 2012)
None